Stimulating workplace learning through training characteristics and motivation to learn - Siti Fardaniah Abdul Aziz,; Mohd. Nasir Selamat, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The present study seeks to identify the efficacy of training characteristics that stimulate motivation to learn; and training effectiveness for workplace learning. Data1 were collected by administering a survey on self-perception from a sample of academic staff in a Malaysian public university. The findings indicated that training design followed by training reputation and familiarity of training content are the most important training characteristics for workplace learning. Interestingly, trainees who perceive training as relevant will also perceive training as reputable. Meanwhile, motivation to learn plays the role of mediator and the option for voluntary attendance plays the role of moderator. The findings can be used to produce training guidelines that ensure training effectiveness not only for workplace learning, but all training programmes in Malaysia.